Decrypting stable‐isotope (δ13C and δ15N) variability in aquatic plants. (10th September 2017) - Chappuis, Eglantine; Seriñá, Vanesa; Martí, Eugènia; Ballesteros, Enric; Gacia, Esperança
Abstract: Variability in C and N stable isotopes has been acknowledged to hinder their use as tracers of food sources in the study of trophic interactions in ecosystems. This is particularly so whenever benthic primary production is substantial (variability in δ 13 C) and the ecosystem under study is affected by human impacts (variability in δ 15 N) in aquatic ecosystems. In this study, we aim to better understand the large and often unexplained variability in the natural abundance of δ 13 C and δ 15 N signatures of aquatic plants by analyzing the isotopic composition of plants from 81 lentic systems from NE Spain in relation to extrinsic (alkalinity, pH, nutrient concentrations, water body typology and basin land use) and intrinsic (functional group, carbon assimilation metabolism, elemental composition) predictors. We have encountered significant plasticity in isotopic signatures of aquatic plants associated with the variation in local conditions at the regional scale. The δ 13 C signature varied from −43.1‰ to −7.5‰ (35.7‰ range) and drivers were both intrinsic and extrinsic. The functional group was the most important factor as it is influenced by different carbon sources. Aquatic plants with leaves in contact with the atmosphere (helophytes, free floating and floating attached; −34.8‰ to −14.6‰) responded in a similar way as terrestrial plants. This contrasted with the enriched mean values of rooted submerged plants (−16.7‰ to −10.5‰) that were more enriched than the described terrestrial C3 range (−34‰ to −22‰) and completely overlapped the terrestrial C4 range (−20‰ to −8‰). Concentration of DIC and pH also emerged as important extrinsic factors driving δ 13 C variability. The δ 15 N signature ranged from −5.2‰ to 20.1‰ (25.2‰ range) and the variability was mostly associated with extrinsic factors such as water body type and basin land use, as they influence both the δ 15 N signature and concentration of the dissolved inorganic nitrogen in the aquatic ecosystems. Only one multifactorial model including the functional group (with the largest contribution), DIC and pH was selected as the best model explaining the variability in δ 13 C signatures of aquatic plants. The final model had a relatively large explained deviance and was consistent with the previous unifactorial results. Two different models were selected as the best models explaining variability in δ 15 N signatures of aquatic plants. The models included the geomorphological type of water body as the variable with the largest contribution, and the percentage of either natural or agricultural coverage in the basin. These results are summarized in a conceptual model showing the predictors and their range and direction of variation. This study shows that extrinsic factors are of greater importance in influencing the stable‐isotope signatures of aquatic plants compared to terrestrial plants, because of varied sources and an often limited isotopic discrimination.